Discontinuous slow crack growth modeling of semi-elliptical surface crack in high density polyethylene using crack layer theory. (1st March 2020) - Wee, Jung-Wook; Chudnovsky, Alexander; Choi, Byoung-Ho
Highlights: Slow crack growth model for HDPE with a surface crack is developed. Crack layer theory is adapted to construct the model for a planar crack. Discontinuous SCG for semi-elliptical surface crack is successfully simulated. Various loading conditions are considered for extensive applications. Abstract: Surface flaws in structural materials are most likely to be generated during service time. One of the most general shapes of surface flaws is the semi-elliptical surface crack. Frequently, the slow crack growth (SCG) of a crack has been fitted based on the conventional Paris–Erdogan relationship. However, in the case of engineering plastics, which generally reveal a severe unrecoverable damage zone at the crack tip, the conventional Paris–Erdogan relationship is not appropriate to describe the SCG of a crack. Especially, SCG kinetics of some engineering polymers such as high-density polyethylene (HDPE) affect the SCG characteristics, i.e. non-conventional discontinuous SCG behavior, which cannot be simulated by conventional Paris–Erdogan relationship. It is known that the crack layer (CL) theory, which deals with driving forces of crack and process zone (PZ) together, can be a good mathematical model to simulate such SCG behavior. In this study, the discontinuous SCG of a semi-elliptical surface flaw in HDPE plate under cyclic tensile stress was simulated using the CL theory. Although the CL theory has the advantage of simulating the discontinuous SCG of HDPE accurately, until now the applications have been concentrated on one-dimensional slow crack growth. In this paper, the CL model for two-dimensional surface crack growth for axial and bending loading conditions was developed for the first time. The proposed model is validated with actual test results, and the role of some key CL parameters on discontinuous SCG behavior of a semi-elliptical surface flaw is investigated by intensive parametric studies.